A case report of TB versus idiopathic granulomatous mastitis with erythema nodosum, reactive arthritis, cough, and headache. (4th December 2020) - Ben Abid, Fatma; Abdel Rahman S. Al Soub, Hussam
Abstract: Tuberculous mastitis (TBM) is relatively rare disease with an incidence ranging between 0.1 and 4%. Most of the cases are culture negative and often mistaken with chronic benign idiopathic granulomatous mastitis (IGM). It is very crucial to distinguish culture negative TBM from other causes of mastitis as the treatment differs tremendously. We describe here in a young woman originally from India and residing in Qatar; a non endemic area of tuberculosis; for more then fifteen years. She presented with 2 months history of right breast mass, followed by low grade fever, dry cough, headache, erythema nodosum, arthritis, and arthralgia. In view of the origin of the patient, positive family history for tuberculosis and positive quantiferon, the patient was started empirically on anti-tuberculous treatment (ATT). One week later she developed paradoxical reaction to ATT. This case illustrates unusual and rare manifestations of primary TBM and highlights the importance of differentiating and treating culture negative TBM from IGM.